The implementation of “Innovate Education” and the “New High School” in the state education network in São Paulo since the pandemic: resignification experiences through pedagogical autonomy - Eiras Rubio, Fernanda; Corti , Ana Paula (The ESPecialist, 2024)
From the educational changes generated by the BNCC in Brazil, without participation of the school communities, the Innovative Education was implemented by the São Paulo`s (SP) state education network during the Corona vírus context. In the less critical period of the pandemic, the New High School was implemented. This research aims to analyze some pedagogical experiences during the curricular changes in SP with a literature review and the methodology of autoethnography (VERSIANI, 2013 and SANTOS, 2017). These experiences demonstrate that despite this new curricular model causes great damage to education, it is possible to reframe the impositions of the system with the pedagogical autonomy ensured by the LDB. This praxis is associated with the decolonial perspective and especially to the autonomous critical feminism within the collective political practices. In the decolonial feminism (LUGONES, 2014), are evidenced pedagogies that strength new ways for the social transformation (CURIEL, 2018).